Treatment of personality pathology through the lens of the hierarchical taxonomy of psychopathology: Developing a research agenda - Mullins‐Sweatt, Stephanie N.; Hopwood, Christopher J.; Chmielewski, Michael; Meyer, Neil A.; Min, Jiwon; Helle, Ashley C.; Walgren, Maggie D. (Personality and mental health, 2020)
Despite the emphasis on evidence‐based treatment for psychological disorders, to date, there has been limited research examining treatment for nine of the 10 categorical personality disorders in DSM‐5 Section 2. This is perhaps not surprising given the complex heterogeneity and co‐morbidity within personality pathology. The hierarchical taxonomy of psychopathology (HiTOP) was proposed to address limitations within the traditional categorical model of the diagnostic system. Within this system are five spectra: detachment, antagonistic externalizing, disinhibited externalizing, thought disorder and internalizing. These foundational personality traits potentially have direct and specific treatment implications. The purpose of this paper is to highlight potential psychotherapeutic and pharmacological treatment recommendations within the personality spectra. Additionally, we outline the advantages of considering the personality science found within dimensional models of psychopathology in clinical assessment and intervention to aid in treatment planning. © 2019 John Wiley & Sons, Ltd.